Young adults' experiences with flexitarianism: The 4Cs. (1st May 2021) - Kemper, Joya A.; White, Samantha K.
Abstract: Meat reduction has important implications for public health and the environment. With people more likely to reduce their meat consumption than eliminate it completely, there is increased interest in flexitarian (reduced meat) diets. Young adults in particular are transitioning towards a flexitarian diet, yet there is very little research on this crucial sub-set of the population. In this research, 23 interviews are conducted with young adults aged 18–35 in New Zealand to explore their lived experiences (i.e., motivations, strategies and barriers) towards flexitarianism. The research finds young adults are encouraged to transition towards flexitarianism due to increased control, through a transition away from home which is enabled through cooking strategies, social support and experimentation. Young flexitarians are motivated to reduce meat consumption due to concern about various individual (health, variety, price, reduce social unease) and altruistic (environment and ethics) motivations. Continued meat consumption is mainly driven by a need to compromise at social gatherings, and due to positive associations with variety, nutrients and fullness as well as taste due to cravings. The findings have several implications for social marketing and public health, particularly around supportive social settings, seeing flexitarianism as a 'not all or nothing approach' (one does not have to be a full vegetarian or a meat eater, but can instead be something in between), positive emotions such as pride associated with meat reduction, and that documentaries and social networks are key triggers for meat reduction.